Gut microbiota compositions and metabolic functions in type 2 diabetes differ with glycemic durability to metformin monotherapy. (April 2021) - Hung, Wei-Wen; Peng, Po; Tsai, Yi-Chun; Jhou, Pei-Syuan; Chang, Chen-Chia; Hsieh, Ching-Chun; Su, Yong-Chao; Dai, Chia-Yen; Hung, Wei-Chun
Highlights: Metformin durability in type 2 diabetes associate with gut microbiota compositions. Microbial intra-group diversity significantly reduce in the metformin durable group. Thiamine and lipopolysaccharide biosynthesis enriched in the metformin durable group. Microbial salvage might increase thiamine synthesis to maintain metformin durability. Abstract: Aims: The metabolic derangements in type 2 diabetes have been attributed to compositional changes in the gut microbiota. Metformin, the first-line treatment for type 2 diabetes, has been found to modulate the gut microbiota. However, no literature has reported the associations between the composition of the gut microbiota and glycemic durability to metformin monotherapy. Methods: A total of 375 patients with type 2 diabetes were recruited, among which 14 and 11 patients were eligible as the metformin durable group and nondurable group, respectively. Fecal samples were collected to analyze the gut microbiota by Illumina sequencing of the 16S rRNA gene, and PICRUSt2 was adopted to infer microbial functional differences. Results: Although the two groups had similar biochemical profiles and microbial metabolites, the pattern of microbiota clustering was different. The intra-group diversity was significantly reduced in the durable group. For the microbial metabolic pathways, the biosynthesis of thiamine and lipopolysaccharide was dominant in the durable group. Conclusions: There were different compositions of gut microbiota with unique microbial metabolic pathways between type 2 diabetes with and without glycemic durability to metformin monotherapy. Microbial salvage by increasing thiamine biosynthesis might be beneficial for the metformin durable group to maintain optimal glycemic control.